2023
DOI: 10.3390/toxics11090745
|View full text |Cite
|
Sign up to set email alerts
|

Association of Per- and Polyfluoroalkyl Substances with Allostatic Load Stratified by Herpes Simplex Virus 1 and 2 Exposure

Yvonne S. Boafo,
Sayed Mostafa,
Emmanuel Obeng-Gyasi

Abstract: Herpes Simplex Virus (HSV) 1 and 2 are persistent infections that affect a significant percentage of United States (US) adults, with 48% having HSV-1 and 12% having HSV-2. Using data stratified by HSV-1 and HSV-2 exposures, this study investigated the association of per- and polyfluoroalkyl substances (PFAS), a group of toxic synthetic organofluorine chemical compounds found in environmental, occupational, and home settings, with allostatic load (AL), an index of chronic physiological stress. Descriptive stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Due to the health burden caused by PFAS exposure, stress has been known to affect the body’s hormonal balance, immune function, and inflammation levels, all of which could potentially play a role in cancer development. For example, research has found a relationship between PFAS exposure and allostatic load, an index of chronic stress [ 9 , 10 , 11 ]. This indicates that the biological response to stress increases when exposed to PFAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the health burden caused by PFAS exposure, stress has been known to affect the body’s hormonal balance, immune function, and inflammation levels, all of which could potentially play a role in cancer development. For example, research has found a relationship between PFAS exposure and allostatic load, an index of chronic stress [ 9 , 10 , 11 ]. This indicates that the biological response to stress increases when exposed to PFAS.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of allostatic load, which represents the cumulative burden of chronic stress and life events, is particularly relevant here. It is hypothesized that individuals with higher allostatic load may exhibit increased sensitivity to the harmful effects of PFAS, thereby elevating their risk for endometrial cancer [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that hepatic disease has a global influence that reaches beyond the healthcare sphere. These diseases represent significant economic and social issues, such as increased healthcare costs, decreased work productivity, chances of mortality, and a lower quality of life for affected persons and their families [ 1 , 2 , 5 ]. Furthermore, the burden of hepatic illnesses does not stop with the patients; it spreads throughout society, affecting careers, employers, and healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is growing concern about the influence of environmental toxins and chemicals on liver health. Within this context, the role of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) has come under scrutiny due to their widespread presence and potential health risks [ 5 ]. This growing problem makes it critical to identify the significant factors contributing to hepatic disorders and their impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation